2017
DOI: 10.1016/j.chempr.2016.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Solution Processing of a Hydrogen-Bonded Ladder Polymer

Abstract: Fang and coworkers report a conjugated ladder polymer featuring a rigid coplanar backbone and self-complementary intermolecular hydrogen bonds. The gramscale synthesis was achieved in three steps with overall 66% yield. Reversible hydrogen-bond protection and cleavage enabled solution-phase characterization of this highly insoluble polymer. Solution-processed thin films demonstrated robust resistance to aggressive solvents after simple thermal annealing. Carbonization of this fused-ring polymer leads to carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 76 publications
3
73
0
Order By: Relevance
“…The thiophene-pyrrole-based LHAs showed that the absorption maxima is redshifted from 298 nm for SN3 (19) to 436 nm for SN10 (27) (Figure 5). 48 The molar extinction coefficient increases with increasing conjugation length.…”
Section: Physical Properties Dependent On Conjugation Lengthmentioning
confidence: 99%
See 1 more Smart Citation
“…The thiophene-pyrrole-based LHAs showed that the absorption maxima is redshifted from 298 nm for SN3 (19) to 436 nm for SN10 (27) (Figure 5). 48 The molar extinction coefficient increases with increasing conjugation length.…”
Section: Physical Properties Dependent On Conjugation Lengthmentioning
confidence: 99%
“…[15][16][17] The insolubility of ladder-type polymers prevents detailed structural characterization and hence understanding of their physical properties. 18,19 To overcome these problems and obtain new ladder structures, the development of efficient and versatile synthetic strategies is needed so that the potential for the ladder molecules and polymers can be fully explored. 20 Actually, very few synthetic strategies toward…”
Section: Introductionmentioning
confidence: 99%
“…The hydrogen nuclear magnetic resonance ( 1 H NMR) titration experiments indicated that this dipeptide has a strong and differential binding affinity for Neu5Ac, Gal, GlcNAc, Man or Glc. Then, L-Asp-L-Phe was grafted onto a branched polyethyleneimine (PEI) main chain (average molecular weight of 10 000 Da) with a grafting ratio of~6% to construct a smart polymeric network, 27 and more details of the synthetic process are displayed in Supplementary Scheme 1. A quartz crystal microbalance with a dissipation monitoring (QCM-D) experiment and corresponding surface stiffness analysis demonstrated that the prepared PEI-g-LAsp-L-Phe (abbreviated PEI-g-DF) thin film displayed satisfactory chemoselectivity for three glucose homologs that only differ in the stereo-orientation of a hydroxyl as well as remarkable adsorption with Neu5Ac, Gal and GlcNAc, which further facilitated the highly selective adsorption of the sialyllactose linkage isomers 28 (that is, core fragments of the sialo-complex-type glycans) and N-linked disialylated bi-antennary glycan (that is, the real glycan appended to a glycopeptide).…”
Section: Introductionmentioning
confidence: 99%
“…[20] As a continuing effort to explore the utility of this synthesis, herein, we report the design and synthesis of a conjugated copolymer consisting of aniline and fluorene repeating unit (poly(aniline-co-fluorene), PAF) that exhibits a high doping level, multi-electron transfer, and excellent solution processability, enabling the formation of thick (>50 µm)…”
mentioning
confidence: 99%